The people in question : citizens and constitutions in uncertain times - Shaw, Jo, 1961- (Bristol University Press, 2020)
At a time of rising populism and debate about immigration, leading legal academic Jo Shaw sets out to review interactions between constitutions and constructs of citizenship. This incisive appraisal is the first sustained treatment of the relationship between citizenship and constitutional law in a comparative and transnational perspective. Drawing on examples from around the world, it assesses how countries' legal, political and cultural processes help to determine the boundaries of citizenship. For students and academics across political, social and international disciplines, Shaw offers an accessible response to some of the most pressing international questions of our age.